Urban vitality assessment at the neighborhood scale with geo-data: A review toward implementation - Liu, Sheng; Ge, Jian; Ye, Xinyue; Wu, Chao; Bai, Ming (Journal of geographical sciences, 2023)
The number of urban vitality assessment studies is rising continuously, owing to the emergence of geographic data. The current literature focuses primarily on evaluation, rather than implementation, of urban vitality. Hence, a scoping review and research agenda are needed for urban vitality research to be more practical. This study aims to fill the research gap by exploring the content and methods of vitality assessment that can make urban vitality research more compatible with policy, planning, and design practice. We chose the neighborhood scale, which is the most practical initiative unit for vitality enhancement. We discovered that the gaps between the current research and practice primarily lie in the diversity of research subjects, the authenticity and comprehensiveness of vitality measurement, and the multi-domain of impact factor analysis. On this basis, we classified the following expandable aspects: (1) multi-type, multi-dimensional, multi-temporal, and implementation-adaptive vitality evaluation; (2) methods reflecting high-quality social interactions and the perceptions of vulnerable groups; (3) how design and urban management impacts vitality; and (4) the synergistic effects of multiple indicators on vitality. Overall, the research content and methodology presented in this paper can help neighborhood-scale vitality assessment to provide more meaningful insights for policy makers and practitioners.